Pembelajaran Kontekstual Melalui Permainan Kelereng pada Siswa Kelas 3A MIN 2 Probolinggo untuk Meningkatkan Pemahaman Konsep Perkalian - Dewi Wahyuning Hikmah; Yusrolana (IBTIDA', 2021)
Learning is said to be good if during the learning process all students are active or participate in answering or asking questions. The learning process is a form of educative interaction, which is an educationally valuable interaction that consciously sets the goal to change a person's behavior and actions. Educational interaction must describe a two-way active relationship between teachers and students with a number of knowledge as the medium. In educative interactions, the elements of teachers and students must be active, it is impossible for an educational interaction process to occur if only one element is active. Active in the sense of attitude, mental, and deed.